CaV1.3 enhanced store operated calcium promotes resistance to androgen deprivation in prostate cancer. (May 2022) - O'Reilly, Debbie; Downing, Tim; Kouba, Sana; Potier-Cartereau, Marie; McKenna, Declan J.; Vandier, Christophe; Buchanan, Paul J.
Highlights: CaV1.3 is upregulated in prostate cancer during androgen deprivation therapy Expression of short 170kDa isoform determines CaV1.3 function in PCa Store operated calcium entry is enhanced through CaV1.3 under androgen deprivation Androgen independent proliferation and survival is linked to CaV1.3 calcium entry CaV1.3 represents a novel oncochannel linked to castrate resistant prostate cancer Abstract: Androgen deprivation therapy (ADT) is the main treatment for advanced prostate cancer (PCa) but resistance results in progression to terminal castrate resistant PCa (CRPC), where there is an unmet therapeutic need. Aberrant intracellular calcium (Cai 2+ ) is known to promote neoplastic transformation and treatment resistance. There is growing evidence that voltage gated calcium channel (VGCC) expression is increased in cancer, particularly CACNA1D /CaV1.3 in CRPC. The aim of this study was to investigate if increased CaV1.3 drives resistance to ADT and determine its associated impact on Cai 2+ and cancer biology. Bioinformatic analysis revealed that CACNA1D gene expression is increased in ADT treated PCa patients. This was corroborated in both in vivo LNCaP xenograft mouse and in vitro PCa cell line models, which demonstrated a significant increase in CaV1.3 protein expression following ADT with bicalutamide. Expression was found to be of a shortened 170kDa CaV1.3 isoform associated with plasma and intracellular membranes, which failed to induce calcium influx following membrane depolarisation. Instead, under ADT CaV1.3 mediated a rise in basal cytosolic calcium and an increase in store operated calcium entry (SOCE). This mechanism was found to promote the proliferation and survival of ADT resistant CRPC cells. Overall, this study demonstrates for the first time in PCa that under ADT specific CaV1.3 isoforms promote an upregulation of SOCE which contributes to treatment resistance and CRPC biology. Thus, this novel oncochannel represents a target for therapeutic development to improve PCa patient outcomes. Graphical Abstract: Graphical Abstract Image, graphical abstract .